Methods for ensuring stability of operating conditions of an electric power system with distributed generation plants - Iliev, Iliya; Kryukov, Andrey; Bulatov, Yuri; Suslov, Konstantin; Beloev, Ivan; Valeeva, Yuliya (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
Modern electric power systems (EPSs) experience an increase in the number of distributed generation plants. These plants can be located far from the center of consumption, which "narrows" the areas of static aperiodic stability, determining the possibility of the existence of the operating mode of the electric power system. Since there can be variations in the operating conditions of distributed generation plants and changes in the areas of static aperiodic stability, it is necessary to use adaptive control algorithms. The presented methods are based on the equations of limit conditions. Reliable convergence of iterative processes is ensured by specifying initial approximations based on the proposed starting algorithms. Modeling of transient processes in the studied EPS was performed for various points in the space of controlled operating parameters in the MATLAB system. It showed the effectiveness of the fuzzy control system when used to adjust the settings of automatic regulators of distributed generation plants. The greatest effect is observed for generator voltage: the transition process time for the first distributed generation installation is reduced by four times, and for the second installation – by 2.3 times; there are no generator voltage fluctuations in transient mode.